Student Savings Decisions Based on Sharia Compliance and Banking Factors: Keputusan Tabungan Mahasiswa Berdasarkan Kepatuhan Syariah dan Faktor Perbankan - Aswin Tanjung, Ditia Azzahra; Harahap, Muhammad Ikhsan; Yanti, Nursantri (Academia Open, 2025)
<article class="text-token-text-primary w-full focus:outline-none scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-testid="conversation-turn-2" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:32rem] @[34rem]:[--thread-content-max-width:40rem] @[64rem]:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="961f8cf4-f3f9-4309-82d1-f1a2581d8a64" data-message-model-slug="gpt-4o"> General Background: Islamic banking has grown significantly in Indonesia, particularly among students seeking Sharia-compliant financial services. Specific Background: Bank Sumut Syariah, as a regional Islamic bank, serves UINSU students whose preferences are influenced by religious and practical factors. Knowledge Gap: While many studies focus on national Islamic banks, limited research explores student behavior toward local Sharia banks like Bank Sumut Syariah. Aims: This study aims to identify and analyze the dominant factors affecting UINSU students’ decisions to save at Bank Sumut Syariah. Results: Using a sample of 100 students and multiple regression analysis, the findings show that Sharia compliance, security, trust, and facilities significantly affect savings decisions, with Sharia compliance being the most influential (B = 0.312). The model explains 60.2% of the variation in saving behavior (Adjusted R² = 0.602), and the research instrument is highly reliable (Cronbach’s Alpha = 0.931). Novelty: This research uniquely integrates four key variables into a localized behavioral model specific to a regional Islamic bank and student demographic. Implications: The results provide strategic insights for Islamic banks to prioritize Sharia integrity and responsive digital services to foster loyalty and align financial practices with students' religious and lifestyle values. Highlight : <article class="text-token-text-primary w-full focus:outline-none scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-testid="conversation-turn-4" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:32rem] @[34rem]:[--thread-content-max-width:40rem] @[64rem]:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="90aa7ad4-78a9-4bbd-80a1-59956f527f51" data-message-model-slug="gpt-4o"> Sharia compliance is the most influential factor in students’ saving behavior. Security, trust, and facilities also have significant roles. The model explains 60.2% of the decision variation using four key variables. Keywords : Sharia Compliance, Security, Trust, Facilities, Saving Decision